Nilai-Nilai Pendidikan Islam Dalam Film Ayat-Ayat Cinta - Aulia Ayu Rohayah; Miftahurrohmah Miftahurrohmah (Turabian: Jurnal Pendidikan Islam, 2024)
Islamic education values are a set of beliefs or feelings in humans that are in accordance with Islamic norms and teachings to create human beings. This research uses qualitative research methods with a content analysis approach. In this study the authors used content analysis techniques, and by using descriptive notes, namely factual information records that describe something as it is and include a detailed and accurate description of the dimensions related to the researcher's aspects. The results of this study found that the Islamic educational values contained in the film Ayat-ayat Cinta are the value of helping, the value of honesty, the value of patience, the value of aqidah, the value of worship, the value of heart education, the value of sincerity, the value of tolerance, the sharia value of polygamy, and the value of akhlakul karimah. The relevance between the values of Islamic education in the film Ayat-ayat Cinta with contemporary Islamic education there are five important aspects that can be taken in Islamic education today, namely presenting a friendly and cool Islam, as well as a solace for the exertion of modern human life that is hedonistic and materialistic, Islam that is tolerant of humans as a whole whatever religion they adhere to, presenting a dynamic, creative, and innovative vision of Islam, the last is building multicultural piety.